State of the University 2016 - Technology Innovations for Learning and Teaching (TILT); Zelezny, Lynnette; Hudson, Abigail; Steele, Ray, Jr.; Castro, Joseph I.
President Castro highlights the University's accomplishments in 2015 and shares his vision for Fresno State's future.